PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Wijaya, Mochammad Hilal; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the influence of intellectual capital which is proxy by Pulic model (VAICâ¢) tothe performance of the company which is proxy by price to book value (PBV) in the company which has intensiveassets of intellectual capital which is automotive company. The population is all automotive companies which arelisted in Indonesia Stock Exchange (IDX). In this research, the sample collection technique has been carried outby using purposive sampling and based on the determined criteria, 8 automotive companies sample which havepublished their financial statement consecutively in 2010-2014 periods have been selected as samples. Thisresearch has been done by using multiple linear regressions analysis and the application of SPSS version 20. Theresult of this research shows that (1) value added capital employed (VACA) has significant influence to the priceto book value (PBV); (2) Value added human capital (VAHU) does not have any influence to the price to bookvalue (PBV); (3) Structural capital value added (STVA) does not have any influence to the price to book value(PBV).Keywords: Intellectual capital, price to book value, value added capital employed, value added humancapital, structural capital value added.